Mitigating Alcohol-Induced Liver Enzyme Alterations in Wistar Rats Through Forced Swimming Exercise - I, Abdul-Kareem Y.; U, Chidiebere; G, Yilgwan; M, Usman Y.; Z, Galam N. (Darul Yasin Al Sys, 2024)
This study investigates the impact of forced swimming exercise on alcohol-induced alterations in hepatic enzyme biomarkers in Wistar rats (mean weight 150-200g). Twenty Wistar rats were randomly divided into four groups of five rats each: a normal control group, an exercise-only group, an alcohol-only group, and an exercise plus alcohol group. The control group received 0.9% normal saline 5 days a week for 12 weeks. The exercise group underwent forced swimming for 5 minutes a day, 5 days a week, for 12 weeks. The alcohol group received 20% ethanol orally at a dose of 2.0g/kg body weight. The combined exercise and alcohol group followed the same protocols as the exercise and alcohol groups. At the end of the 12-week period, all animals were euthanized, and blood samples were collected for analysis of hepatic enzyme biomarkers, including ALT, AST, and GGT, using an automated serum biochemistry analyzer. Results showed significant elevation of hepatic enzyme biomarkers in the alcohol-only group, while the normal control, exercise-only, and exercise plus alcohol groups exhibited decreased enzyme levels. These findings indicate that exercise mitigates alcohol-induced liver enzyme alterations in adult male Wistar rats. The study suggests that exercise training may be effective in alleviating liver damage from chronic alcohol consumption and could potentially prevent liver failure and hepatocellular carcinoma.